Match demands, anthropometric characteristics, and physical qualities of female rugby sevens athletes. A systematic review - Sella, S. F.; McMaster, T. D.; Beaven, M. C.; Gill, D. N.; Hébert-Losier, K. (The Journal of Strength and Conditioning Research, 2019)
Since the inclusion of rugby sevens in the 2016 Olympic Games, the popularity of women's rugby sevens has grown rapidly worldwide. This systematic review aimed to summarize the scientific literature addressing the match demands, anthropometric characteristics, and physical qualities of female rugby sevens athletes and to highlight differences between competition levels and playing positions. Four electronic databases were searched, as were the reference lists and key journals. Hedges' g effect sizes with 95% confidence intervals were calculated to evaluate differences between elite and nonelite athletes, and backs and forwards. Twenty-seven studies met inclusion criteria and scored 68 ± 13% upon quality assessment. Comparisons between groups were restricted to variables where data were available. Greater running demands and intensities, number of sprints and accelerations, but lower physiological responses characterized international matches compared with nationals. At international level, backs demonstrated greater running demands and intensities, number of sprints, and physiological responses than forwards. Elite athletes were leaner, taller, and displayed superior physical qualities (e.g., maximal speed, power, upper-body strength, and aerobic capacity) compared with nonelite athletes. At elite level, forwards were heavier and displayed greater upper-body strength, whereas backs showed greater acceleration and maximal speed abilities. The specific match demands and physical requirements of female rugby sevens athletes competing at different playing levels and playing positions must be considered for developing effective training programs.